Answer:
Step-by-step explanation:
Simplifying
2x + 13 = 0
Reorder the terms:
13 + 2x = 0
Solving
13 + 2x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-13' to each side of the equation.
13 + -13 + 2x = 0 + -13
Combine like terms: 13 + -13 = 0
0 + 2x = 0 + -13
2x = 0 + -13
Combine like terms: 0 + -13 = -13
2x = -13
Divide each side by '2'.
x = -6.5
Simplifying
x = -6.5
Answer:
Step-by-step explanation:
the following equation to show the height of the plant f(n), in cm, after n days:
f(n) = 8(1.05)^n
Part A: When the scientist concluded his study, the height of the plant was approximately 11.26 cm. What is a reasonable domain to l
Answer:
corresponding
Step-by-step explanation:
because they are in the same place on both intersections. now if u ask me doggo deserve breinliest pwease ;-;
Hello!
Distance between two points (2,9) and (6,3) -
<span>1. Take the Absolute Difference between the X points 2 and 6. The Absolute Difference is 4. </span>
<span>2. Square 4 = 16 </span>
<span>3. Take the Absolute Difference between the Y points 9 and 3. The absolute Difference is 12. </span>
<span>4. Square 12 = 144 </span>
<span>5 Add 144 + 16 = 160 </span>
<span>6. Take the Square root of 160 </span>
<span>12.6491106407
Hope this Helps at least! :)</span>